Rubber Industry Wastewater Treatment Using A Combination Of Ozonation And Modified PES-Nano ZnO Membranes - Enny Nurmalasari; Miftahul Khairati; Tutuk Djoko Kusworo (Universitas Ahmad Dahlan, 2022)
Until now, the application of a combination of biological, physical, and chemical methods to eliminate contaminants from the rubber industry wastewater has not been reported. The purpose of our investigation is to analyze the use of membrane techniques and the effect of pre-treatment of industrial rubber wastewater—pre-treatment by ozone on the performance of the modified PES-nano ZnO membrane. Modified PES-nano ZnO membranes were made with phase inversion techniques and membrane performance based on flux and rejection. Filtration processes with cross-flow filtration systems and ozonation time variations were 1, 2, 3 hours. The ozonation process influenced membrane rejection. The membrane rejection value increased to 89.6%, and ammonia decreased to 4.3 mg/L. The flux value increased to 10.2 L.M-2.h-1 in 1h Ozonatian and decreased with the increasing of filtration time. Pre-treatment with ozonation can increase membrane selectivity and extend membrane life during the filtration process due to reduced fouling. The pre-treatment process time with 3 hours-ozonation was the most violent rejection even though the flux value has decreased